The Syrian Refugees in Lebanon: Moving Towards Securitization - Heavy Nala Estriani (Jurnal Hubungan Internasional, 2019)
This paper analyzes Lebanese policy towards Syrian refugees within their country. The prolonged conflict in Syria has generated a large-scale influx of refugees that contributed to the addition of 1.5 million to 4.5 million Lebanon population. While other Middle Eastern countries such as Jordan and Turkey responded by accepting the arrival of these refugees, Lebanon took the opposite response. Through the analysis of securitization theory and the nexus between migration and demographic balance, it can be understood that the Lebanese Government uses a speech of act strategy in conducting securitization. Speech of act is carried out through political discourse and the role of the media in portraying refugees as an existential threat that require special measure to handle them. Lebanon also uses the issue of demographic change, sectarian balance, and the emergence of the new conflicts, as issues that threaten Lebanon domestic stability and security.